2013
DOI: 10.1016/j.bbadis.2012.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid induces increased BACE1 expression and Aβ formation

Abstract: The abnormal production and accumulation of β-amyloid peptide (Aβ), which is produced from amyloid precursor protein (APP) by the sequential actions of β-secretase and γ-secretase, are thought to be the initial causative events in the development of Alzheimer’s disease (AD). Accumulating evidence suggests that vascular factors play an important role in the pathogenesis of AD. Specifically, studies have suggested that one vascular factor in particular, oxidized low density lipoprotein (oxLDL), may play an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 48 publications
1
29
0
1
Order By: Relevance
“…LPA enhances site-specific pathogenic tau phosphorylation, leading to GSK3-mediated growth cone collapse in neurons (Sayas et al, 1999). LPA also increases β-secretase activity, leading to elevated Aβ production (Shi et al, 2013). Gintonin, a bioactive fraction isolated from ginseng that has been reported to improve cognition in AD, is composed of protein-bound LPA that can activate LPA 1-5 .…”
Section: Stressors and Neuropsychiatric Disordersmentioning
confidence: 99%
“…LPA enhances site-specific pathogenic tau phosphorylation, leading to GSK3-mediated growth cone collapse in neurons (Sayas et al, 1999). LPA also increases β-secretase activity, leading to elevated Aβ production (Shi et al, 2013). Gintonin, a bioactive fraction isolated from ginseng that has been reported to improve cognition in AD, is composed of protein-bound LPA that can activate LPA 1-5 .…”
Section: Stressors and Neuropsychiatric Disordersmentioning
confidence: 99%
“…A recent study has demonstrated the existence of a positive correlation between PKC signaling cascade activation and increased BACE1 expression in fibroblasts and neuroblastoma cells, thus suggesting that PKC signaling cascades may be involved in BACE1 expression in vascular endothelial cells2627. To gain insight into the potential signaling pathways regulating BACE1 expression and protein sialylation levels, phospho-PKC δ and PKC δ protein levels were determined via western blotting analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have confirmed that PKC signaling is involved in BACE1 upregulation in neuroblastoma and fibroblast cell lines2627. It is well known that PKC activation is induced by TNFR members, such as TNFR1, FAS (TNFRSF6), OX40, and TRAIL-R1/240.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, oxidized lipoproteins have been identified as a possible oxidative stressor in the brain leading to neuronal cell death in AD [42]. LPA is the most bioactive fraction of oxidized low-density lipoprotein [43]. It has an important signal function and has been linked to the pathogenesis of AD as in vitro results suggest they support tau phosphorylation and raise levels of β-secretase, leading to increased Aβ production [43], [44], [45].…”
Section: Discussionmentioning
confidence: 99%
“…LPA is the most bioactive fraction of oxidized low-density lipoprotein [43]. It has an important signal function and has been linked to the pathogenesis of AD as in vitro results suggest they support tau phosphorylation and raise levels of β-secretase, leading to increased Aβ production [43], [44], [45]. Moreover, LPAs have been identified as important factors in vascular development, atherosclerosis, and atherotrombogenesis [46], [47], [48].…”
Section: Discussionmentioning
confidence: 99%